Pengaruh Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada Perusahaan Sektor Telekomunikasi - Ardana, Vionita Dintri; Mardiana, Mardiana (IJAcc, 2025)
This study analyzes the effect of Return on Assets (ROA) and Return on Equity (ROE) on Net Profit Margin (NPM) at PT Telkom Indonesia (Persero) Tbk. (2018–2023). Quantitative methods, financial ratios, and statistical tests were conducted using SPSS. The results indicate that ROE significantly affects NPM (sig = 0.021 < 0.05), while ROA is not significant (sig = 0.871 > 0.05). Simultaneously, ROA and ROE jointly affect NPM (sig = 0.011; F-calculated 28.166 > F-table 2.732). Equity utilization (ROE) is a key determinant of financial performance, while asset efficiency (ROA) is relevant in combined analysis. This study underscores the strategic importance of managing assets and equity to enhance profitability and investor trust. Keywords: Financial Report, Profitability Ratio, Financial Performance.